2017
DOI: 10.7566/jpsj.86.023702
|View full text |Cite
|
Sign up to set email alerts
|

Hall Effect in the Vortex Lattice ofd-Wave Superconductors with Anisotropic Fermi Surfaces

Abstract: On the basis of the augmented quasiclassical theory of superconductivity with the Lorentz force, we study the magnetic field dependence of the charge distribution due to the Lorentz force in a d-wave vortex lattice with anisotropic Fermi surfaces. Owing to the competition between the energy-gap and Fermi surface anisotropies, the charge profile in the vortex lattice changes dramatically with increasing magnetic field because of the overlaps of each nearest vortex-core charge. In addition, the accumulated charg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…A somewhat different approach has been developed in a series of works by Kohno et al [36], [37], [38] who explored the physics of the Lorentz force in superconductors. They studied The field dependence of the charge density at the core center in their theory is well described by the non-monotonic field dependence:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A somewhat different approach has been developed in a series of works by Kohno et al [36], [37], [38] who explored the physics of the Lorentz force in superconductors. They studied The field dependence of the charge density at the core center in their theory is well described by the non-monotonic field dependence:…”
Section: Resultsmentioning
confidence: 99%
“…This article is devoted to galvanomagnetic effects ( , ) in a mixed state of an electron- Our research reveals that theoretical developments to describe the studied experimental situation on the Josephson vortices with intrinsic pinning are insufficient (for ) or even completely absent (for ). To interpret the data on ( ) we use some theoretical concepts developed for the Abrikosov vortices [36] - [38] that still requires a further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our previous works have shown that the charge accumulation by the Lorentz force in the core is strongly enhanced compared with that of an isolated vortex as the external magnetic field increases from a lower critical field. 37,38) Thus, the contribution of the Lorentz force to the core charge may become dominant over the contributions of other forces in finite magnetic fields. Hence, we should study the magnetic-field dependence of the vortex-core charging due to the three forces by solving these augmented Eilenberger equations with three forces for the vortex lattice system.…”
Section: Discussionmentioning
confidence: 99%
“…29) Very recently, augmented Eilenberger equations incorporating the Lorentz force in the Matsubara formalism were derived 36) and used to calculate the vortex-core charging due to the Lorentz force as functions of the temperature 36) and magnetic field. 37,38) More precisely, the component of the magnetic Lorentz force that balances the Hall electric field may be missing from the standard Eilenberger equations. It is known that the component of the magnetic Lorentz force that balances the hydrodynamic force exists in the Ginzburg-Landau (GL) equations.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is worth noting that ρ(0) has been shown to have a strong magnetic-field dependence with a peak structure and can be enhanced significantly over the value of an isolated vortex as the magnetic field is increased. 7,8) Hence, it is not appropriate to conclude that the Lorentz-force contribution is negligible in all cases.…”
mentioning
confidence: 99%